1990
DOI: 10.1007/bf00278577
|View full text |Cite
|
Sign up to set email alerts
|

Betaxolol: a pilot study of its pharmacological and therapeutic properties in pregnancy

Abstract: Twenty two pregnant women with mild to moderate hypertension were treated with betaxolol (10-40 mg/day), a cardioselective beta adrenoceptor blocking agent. The analysis of the changes from the baseline confirmed the antihypertensive effect of the drug with a mean decrease in SBP of 11.8 mm Hg and in DBP of 8.3 mm Hg. A diastolic BP less than 90 mm Hg was obtained in 20 patients after the first day of therapy. Fetal safety, assessed by ultrasonography and cardiotocographic recording was excellent. The 22 mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Preliminary data from studies run in the last 30-60 days of pregnancy suggest that the same can be concluded for the last trimester (Boutroy et al 1990).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Preliminary data from studies run in the last 30-60 days of pregnancy suggest that the same can be concluded for the last trimester (Boutroy et al 1990).…”
Section: Discussionmentioning
confidence: 65%
“…The clinical effects of the treatment are reported in detail elsewhere (Boutroy et al 1990). At the last administration preceding delivery, nineteen patients received 10 mg betaxolol, six had 20 mg, two took 30 mg and one received 40 mg.…”
Section: Findings In Mothersmentioning
confidence: 99%
“…In our study, the metabolite profile of the preterm mice was altered, and differential metabolites were associated with signaling pathways including pyruvate metabolism. Among the top 20 metabolites with the highest VIP scores under POS and NEG modes, respectively, betaxolol has been reported to efficiently treat the arterial hypertension in pregnancy [ 51 , 52 ]. Another metabolite, Arbekacin, is classified as an aminoglycoside antibiotic that exhibits stability against the majority of aminoglycoside-inactivating enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from effective HR, BP and MSNA control in hypertension-related tachycardia, therapy with betaxolol has been found favorable in reducing maternal BP without any deleterious effect on the fetus and the newborn [69]. Furthermore, recently a large case-control study in Taiwan found that patients with chronic obstructive pulmonary disease (COPD) taking selective beta-blockers had a lower risk of severe exacerbations compared to patients with COPD who experienced a higher risk of severe exacerbations during an increased mean daily dose of non-cardioselective beta-blockers [70].…”
Section: Effects Of Beta-blockers On Sympathetic Activation In Hypertmentioning
confidence: 99%